Could it have been a success if they had built it? A reflective assessment of the ABC farm business plan - Bausch, Angela M. (Kansas State University, 2016)
Business plans are a necessity for new ventures. The plan helps to set goals for the business, establishes a good product and customer base, looks at competition, provides management strategies and develops a financial plan and succession/exit strategy. This thesis assesses the business plan that was developed for a 9,300 acre farm in Southwestern Wisconsin from an ex post perspective when assumptions about the future have been realized. It assesses the strategic direction, objectives and financial projections that were made and the assumptions that underlay the projections. The research provides a discussion of a family farming operation that ultimately became a banking investment at the cost of many family members’ lifestyles. The farm did continue on, but not with the same operators that had goals to build a new venture from the existing one. This research evaluates the financial information to determine whether the farm could have been a feasible proposition under the specified conditions. Also, the business plan is evaluated using hindsight information to assess the errors in assumptions and their effects on the projected cash flows, profitability and balance sheet situations. The research assesses the role that the template approach to the business planning process played in the results, and explored if the process model or the Cascade Approach® might have produced different recommendations. The entrepreneurial behaviors under uncertainty are discussed and evaluated, with the hubris being an underlying factor in the plan. It is concluded that the assumptions entrepreneurs make are often over-optimistic. There is, therefore, a need to temper entrepreneurs’ enthusiasm about their projects with reality to control their natural hubris.
Keywords: Farm management; Strategy; Budget; Business Plan; Risk Management; Agriculture, General (0473)